1963
DOI: 10.1063/1.1729357
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetism in NiTiO3

Abstract: The effective internal field in NiTiO3 as a function of temperature has been determined from zero-field resonance absorption in a powder sample at millimeter wavelengths. Assuming a g value of 2, the resonant frequency (187 kMc) leads to an effective field at 4.2°K of approximately 67 kG. The temperature dependence fits within experimental error a Brillouin function for S = 1, with a Néel temperature of 22°K. From dc susceptibility data, a Néel temperature of 23°K is obtained and an exchange field of approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1963
1963
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…Our data for NiTiO 3 show that a lambda-shaped low-temperature heat capacity anomaly occurs at around 26 K (Figure 2), coinciding with the antiferromagnetic transition [15,16,39]. In a similar fashion, CoTiO 3 exhibits a low-temperature heat capacity anomaly peaking at 37 K, which is in excellent agreement with the old structural and magnetic data [18,40].…”
Section: Resultssupporting
confidence: 88%
“…Our data for NiTiO 3 show that a lambda-shaped low-temperature heat capacity anomaly occurs at around 26 K (Figure 2), coinciding with the antiferromagnetic transition [15,16,39]. In a similar fashion, CoTiO 3 exhibits a low-temperature heat capacity anomaly peaking at 37 K, which is in excellent agreement with the old structural and magnetic data [18,40].…”
Section: Resultssupporting
confidence: 88%
“…The magnetic structures for a selection of them are depicted in Figure 2.4. Below the Néel temperatures, magnetic moments in NiTiO3 (23-26 K) [102,103] and CoTiO3 (37 K) [103] order ferromagnetically within each layer of Ni 2+ /Co 2+ , with non-magnetic layers of Ti 4+ separating the antiferromagnetic coupling along the c axis, similar to FeTiO3 (Figure 2.4 i). Contrary to FeTiO3, the moments are directed perpendicular to the c axis.…”
Section: Selected Compounds Related To Fe2o3 and Fetio3mentioning
confidence: 99%
“…A FM R in uniaxial ilmenites has been, observed by Heller and co workers [42,43] in the range of 2 to 4 mm wavelength radiation. Results for M n T i0 3 (for which K is positive) for both powder and single-crystal materials were discussed by Stickler and Heller [42].…”
Section: Uniaxial Antiferromagnetsmentioning
confidence: 87%
“…Results for M n T i0 3 (for which K is positive) for both powder and single-crystal materials were discussed by Stickler and Heller [42]. More recently Heller et al [43] have observed A FM R in powders of N iT i0 3 for which K is negative, and the spins are therefore aligned in the [111] plane. More recently Heller et al [43] have observed A FM R in powders of N iT i0 3 for which K is negative, and the spins are therefore aligned in the [111] plane.…”
Section: Uniaxial Antiferromagnetsmentioning
confidence: 92%